Epidemiological Situation on Cholera in the Russian Federation in 2023 and Forecast for 2024 - A. Yu. Popova; A. K. Noskov; E. B. Ezhlova; V. D. Kruglikov; E. V. Monakhova; O. S. Chemisova; A. A. Lopatin; S. M. Ivanova; O. A. Podoynitsyna; A. S. Vodop’yanov; D. A. Levchenko; I. V. Savina (Проблемы особо опасных инфекций, 2024)
The paper presents an analysis and assessment of risks of complication of epidemiological situation regarding cholera in the Russian Federation and a forecast for 2024. It briefly characterizes the dynamics of the epidemic process around the world during the last decade (2013–2022). The forecast of cholera importation into the Russian Federation, due to activity of the epidemic process in endemic countries, has been confirmed. In 2023, two cases of cholera importation from India were reported. It was established that the toxigenic strains isolated from patients belonged to the currently dominant in the world “post-Haitian” group, including in India and Bangladesh, with the genotype ctxB7 tcpACIRS rtxA4a VSP-IIΔ0495-0512. Furthermore, non-toxigenic Vibrio cholerae O1 strains were isolated from samples of biological material from persons arriving from India, containing preCTX prophage and distinct from the strain (ctxAB– tcpAEТ–) isolated from a patient with acute intestinal infection (Zaporozhye Region, Melitopol). Nontoxigenic NAG vibrios were isolated from 13 patients with acute intestinal infections, which is 1.9 times more than in 2022. Regardless of importations, a strain of V. cholerae O1 (ctxB1+tcpAEТ) of the “pre-Haitian” group was isolated from a water sample of a surface reservoir. 52 non-toxigenic V. сholerae O1 strains were found on the territory of 11 constituent entities of the Russian Federation, which is 18.9 % more than in 2022. In 2024, epidemiological risks of cholera importation from endemic countries to any administrative territory of the Russian Federation remain. The risks of epidemic manifestations of cholera are especially high in the territories of the constituent entities of the Russian Federation which are under ongoing emergency, due to migration processes, and the impact of other risk-forming factors that contribute to an increase in the degree of contact of the population with water bodies contaminated with cholera vibrios. If epidemic foci of cholera are to emerge in a neighboring country, there will be a high probability of spread of this infection in the stated constituent entities of the Russian Federation and in other territories of southern Russia. In the absence of epidemic manifestations of cholera, the possibility of occasional detection of toxigenic O1 serogroup strains in water samples due to unidentified introductions from cholera-affected areas cannot be ruled out.